THE ROLE OF SOCIAL CAPITAL FOR BUMDES IN WASTE MANAGEMENT IN MIAGAN VILLAGE, MOJOAGUNG DISTRICT, JOMBANG REGENCY - Faizin, Muhammad Luqman (Airlangga Development Journal, 2024)
One of the important problems that often occur in rural communities is attention to waste. Data on waste in Indonesia from 2019 to 2020 is observed to continue to increase in number. Waste data for that year was 66-67 tons in 2019 and increased to 67.8 tons in 2020. Therefore, it is necessary to have BUMDes that are willing to manage waste and benefit from these activities. This study will focus on discussing the problem of the role of BUMDes in improving the residents' economy by empowering and managing waste by Kreto Makmur BUMDes. The type of research used in this research is qualitative research. This research uses a case study approach. The instruments of this research are interview guidelines and document collection related to waste management by BUMDes. The data analysis process is carried out continuously (cyclically) since the researcher enters the field until the research activity ends. The analysis techniques of research results are: (1) data collection; (2) data reduction; (3) data presentation; (4) conclusion/verification. The results of this study are BUMDes have a significant role in empowering the Miagan Village community, one of which is waste management. From this management, the village government and BUMDes are able to contribute PAD of 6,000,000 rupiah per month.